Effect of NPK Levels on Potato (Solanum tuberosum L.) Tuber Yield Attributes in the North Zone of Bihar, India - Mayank Mani Tripathi; Mayank Srivastava; Amrendra Kumar; Utkarsh Singh; Rupali Singh; Arpit Singh (Archives of Current Research International, 2024)
This field research was carried out on a potato crop of the cultivar Kufri Lalit in the Rabi season of 2021–2022. at research farm of TCA, Dholi (Muzaffarpur), Bihar13 treatments and 3 replications were used in this experiment’s randomised block design. The experimental location had a sandy loam texture, a reaction pH of 8.47 that is alkaline a low organic carbon content of 0.43%, and accessible N (223 kg ha-1). However, P (16.95 kg ha-1) and K (131.46 kg ha-1) availability is moderate. The varying levels of key nutrients had a substantial impact on all growth and yield parameters, including percent emergence, plant height, shoot and leaf number plant-1, dry matter accumulation, tuber bulking rate and yield. Among all treatments, treatment T10 (240N, 120P2O5 and 150K2O kg ha-1) recorded highest per cent emergence (94.00 %), plant’s height (44.27), shoot’s number plant-1 (5.60), leave’s number plant-1 (56.30), tuber yield (26.53 t ha‑1) and treatment T10 also recorded statistically at par with treatment T6.